Le plurilinguisme dans les Moocs : profils d'usagers et fonctions du sous-titrage - Mariana Fonseca; Laurent Gajo (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Moocs ("massive open online courses") not only provide a new basis for teaching, especially at university level, but can radically change the dynamics of knowledge and education by promoting more uniform and global approaches to teaching. This article seeks to study the conflict between contextualization and globalization, and focuses on the use and functions of subtitles in Moocs, from the point of view of their users. It is part of a research project we are carrying out about the place of multilingualism– and multiculturalism– in Moocs.As regards diversity of languages, our work has helped show that, unlike what is commonly believed, languages do not only serve to communicate knowledge (vehicular function), but also play a key part in producing it (constitutive function). Furthermore, the analysis of our questionnaires shows that Mooc users may appreciate the subtitles to learn both the content and a new language.We conclude the article by encouraging Mooc designers to use a variety of voices, in their respective scientific and educational languages and cultures.